A low Power Wireless Interaction System using IFDMA in ZigBee Communication - Allin Joe, D; Karthikumar, R; Pavithra, P (International Journal of Computer Sciences and Engineering, 2025)
In this paper, a new display technology which is more power efficient and provides less interference along with interaction between users is designed. It displays the data entered in touch screen to the connected nodes and vice versa. The input data is entered in touch screen by touching the screen or using a stylus. The touch screen system has a built in data buffer that enables the user to enter data without waiting for the touch screen to be refreshed. When touch screen is refreshed, data from data buffer is sent to a computer and processed. The computer stores the data which is received from the data buffer and transmits the data to connected nodes through ZigBee transceiver. A maximum of 65,536 nodes can receive the data that is transmitted from the ZigBee transceiver within a range of 100 meters. A node can be added or removed easily from the computer by using their IP address which also decreases the interference between nodes of adjacent networks. ZigBee networks are more power efficient and can determine the pending data available in it. Data is received in the connected nodes via ZigBee transceiver attached in them. The nodes also have the capability to transmit messages by their ZigBee transceiver which is displayed in a segment of the screen. Hence an interaction between the users is enabled. If data in a node gets lost, it can be retrieved from the personal computer (PC) itself. This technology can augment the active interaction between the users in classroom and video conferencing. Embedded C and JAVA programming languages are used for the implementation.